PERENCANAAN EKSPOR PERMEN SUSU KARAMEL - Gabriel Willy Widyatama; Geraldo Oktavian; Josafat Gracia Ginting; Melise Mega Anggraini; Stevani Natalia Harianto; Wily Suryani Mega Putra (Journal of the Community Development in Asia (JCDA), 2018)
The market for economic activities is not only limited to Indonesia, but also international to become international business. One of the activities for market expansion is to export products to the international market. Koperasi SAE Pujon is the largest supplier of raw cow milk in East Java (98% of all East Java in 2018) which will be aimed at export planning for one of its products, Caramel Milk Candy. Caramel milk candy is a product made from milk and a caramel mixture compacted into candy. The planned export of caramel milk candy will be aimed at one of the countries with the highest population in the world, namely China (1.386 billion people in 2018) while taking advantage of the opportunity that the Chinese government issued a policy of reducing import duties (17.3% to 7.7%) . The concept of marketing strategies utilizes the ability of cooperative relations with other institutions to assist cooperatives in promoting their products, and cooperatives as vendors. The process of shipping goods through international shipping services that has an export license for goods to be exported such as DHL, Pos Indonesia, etc., but the cost will be cheaper if the calculation based on container, not per kilograms, except for sending product samples to importers . Recruitment process for adding more workers to support production and something else that make the product marketed, will be carried out as needed. Financial Capital is done in two ways, credit to banks or using savings or cooperative cash. Keyword : international business, milk, caramel milk candy, export, export license, recruitment, financial.